Students’ Perception toward the Use of Note-Taking Strategy in Listening Class - Soumokil, Jeclyn Claudia; Nikijuluw, Renata C. G. V.; Lekatompessy, Felicia Miranda (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2021)
As one of the receptive English skills, listening has a significant role as a primary skill for daily communication. Despite its importance, the requirement for doing listening tasks in an academic context has to lead the students to use more practical and effective listening strategies to improve their listening skills and competence, as well. The purposes of this study were to investigate students’ perception towards Note-Taking used in doing a listening activity at listening class, also to find out the benefits and difficulties of note-taking for students. This study used a survey research design by integrating a mixed-method, in which the data was analyzed in qualitative and quantitative ways. The participant of the study was students of English Education Study Program of Pattimura University in the academic year 2017. Classroom observation, a questionnaire, and interview were employed as the techniques in collecting the data. The result showed that 90% of the students have a positive attitude that note taking is important for them to gain information easily. Besides, to see the benefit and difficulties, students’ response that they get more benefits than difficulties in using note-taking enable the students to do the listening activities as being required.